The Effect of Intensive Plyometric Training on the Development of Specific Endurance and Performance in the 110-Meter Hurdles for Youth - Ahmed Shakir Ferman; Hamzah Abduiadheem Hamzah (Penerbit Jurnal Indonesia, 2025)
One exciting sporting event that requires speed, strength, and adrenaline is the 110-meter hurdles. Since the runner's speed starts to decrease in the 110-meter hurdles race at the beginning of muscle strain, which is determined at some point during the total distance of the race, and this stress affects the level of achievement, the researcher sees a weakness in both speed endurance and strength endurance, which is related to the quality of The significance of researching this came from preparing intensive trainings in the style of In order to determine the effects of plyometric training on the special endurance and performance of 110-meter hurdle runners, this study employed an experimental design with a two-group design. The participants were young athletes from Diwaniya Athletics Clubs; the sample size was ten athletes between the ages of eighteen and nineteen. The researchers then divided the participants into two groups, with five competitors in each. If the variables in question are well matched, we should expect good results from this setup. Results The dimensional test yields a tangible distinction in performance between the two groups, but the explosive strength, speed-associated force, and speed stamina of the experimental group benefited relatively greater from plyometrics training than those of the control group.